Bibliometric Web of Science and Google Trends analysis of multi-criteria decision analysis within the built environment - Smith, Kyle Abbott; Mostafiz, Rubayet Bin; Friedland, Carol; Nahmens, Isabelina (Frontiers in Built Environment, 2025)
This research aims to leverage existing data sources to provide new insights into the usage of Multi-Criteria Decision Analysis (MCDA) in the built environment without creating a new data collection process. The study is focused upon built environment vocations, spanning the disciplines of architecture, construction management, urban planning, real estate, facilities management, and the numerous engineering domains that support capital projects. The method of the study utilized Google search engine data from Google Trends and academic literature metadata from Web of Science, which was analyzed using Bibliometrix via the Biblioshiny interface. These datasets were cross-referenced with original data collected from a Qualtrics delivered industry questionnaire to develop a more comprehensive understanding of MCDA adoption within the built environment. The research presents a ranked list of MCDA methods used within built environment vocations in order of level of adoption, with the top five being PROMETHEE, House of Quality, Monte Carlo Simulations, TOPSIS, and Utility Theory. The results include Biblioshiny visualizations for MCDA methods studied within built environment academic papers and findings related to tool associations via key clusters, such as GIS and drone based data collection tool usage, in concert with MCDA methods. The paper presents evidence that MCDAs are more frequently used in environmental science, geography, management, and sustainability studies within the built environment relative to other design or construction oriented use cases. By integrating diverse data sources—academic publications, search engine trends, and industry responses—the research explores a multi-faceted perspective on the current state of MCDA usage, highlighting the gaps between academic focus, industry practices, and public interest. The research notes that MCDAs are often considered on an individual basis instead of approached broadly as a set of mathematical tools, possibly serving as a barrier to a more expansive understanding of the means and methods practitioners might employ.